2013
DOI: 10.1371/journal.pone.0076678
|View full text |Cite|
|
Sign up to set email alerts
|

Construction and Characterization of Normalized cDNA Libraries by 454 Pyrosequencing and Estimation of DNA Methylation Levels in Three Distantly Related Termite Species

Abstract: In termites, division of labor among castes, categories of individuals that perform specialized tasks, increases colony-level productivity and is the key to their ecological success. Although molecular studies on caste polymorphism have been performed in termites, we are far from a comprehensive understanding of the molecular basis of this phenomenon. To facilitate future molecular studies, we aimed to construct expressed sequence tag (EST) libraries covering wide ranges of gene repertoires in three representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…This transcriptome is assembled from whole body tissue mRNAs sampled from three different North American populations. As such, it provides a reasonable estimate of gene composition and expression for this species that compliments prior genomic studies of Reticulitermes (Dedeine et al, 2015;Hayashi et al, 2013;Mitaka et al, 2016;Raychoudhury et al, 2013;Scharf et al, 2003;Scharf et al, 2005;Scharf et al, 2017;Sen et al, 2013;Steller et al, 2010; and other termites (Huang, Sun, Zhou, & Lei, 2012;Ishikawa et al, 2010;Korb et al, 2015;Koshikawa et al, 2005;Poulsen et al, 2014;Terrapon et al, 2014;Wu et al, 2016). Established indicators of transcriptome quality such as N50 value and average gene length generated for the present assembly (Table 3) are consistent with benchmark expectations for non-model organisms (Francis et al, 2013).…”
Section: Reticulitermes Flavipessupporting
confidence: 83%
See 1 more Smart Citation
“…This transcriptome is assembled from whole body tissue mRNAs sampled from three different North American populations. As such, it provides a reasonable estimate of gene composition and expression for this species that compliments prior genomic studies of Reticulitermes (Dedeine et al, 2015;Hayashi et al, 2013;Mitaka et al, 2016;Raychoudhury et al, 2013;Scharf et al, 2003;Scharf et al, 2005;Scharf et al, 2017;Sen et al, 2013;Steller et al, 2010; and other termites (Huang, Sun, Zhou, & Lei, 2012;Ishikawa et al, 2010;Korb et al, 2015;Koshikawa et al, 2005;Poulsen et al, 2014;Terrapon et al, 2014;Wu et al, 2016). Established indicators of transcriptome quality such as N50 value and average gene length generated for the present assembly (Table 3) are consistent with benchmark expectations for non-model organisms (Francis et al, 2013).…”
Section: Reticulitermes Flavipessupporting
confidence: 83%
“…For the transcriptome as a whole, the proportion of unknown but presumably functional genes is ∼20% (Table 4). This proportion is lower than previous R. flavipes EST-sequencing (Steller et al, 2010;Tartar et al, 2009), and is comparable to other termite RNA-seq studies (Dedeine et al, 2015;Hayashi et al, 2013;Wu et al, 2016). The set of 93 casteinformative genes presented in Figure 1 are well characterized by homology from other organisms in the SwissProt database: only n = 29 genes (31%) did not have a strict homolog (Table S2).…”
Section: Reticulitermes Flavipessupporting
confidence: 68%
“…Partial cDNA sequences of Met , Kr‐h1 and Br‐C homologues ( RsMet , RsKr‐h1 and RsBr‐C ) were obtained from normalized cDNA libraries of R. speratus (Hayashi et al ., ). We designed gene‐specific primers [ RsMet for rapid amplification of cDNA ends (RACE) PCR, RsKr‐h1 and RsBr‐C for subcloning; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid sequence is written under the cDNA sequence. Shaded areas show the partial cDNA sequence obtained from normalized cDNA libraries (Hayashi et al, 2013). The boxed area and solid underline show the sequences of the Per-Arnt-Sim (PAS) and basic-helix-loop-helix (bHLH) domains, respectively.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Results also suggested that DNA methylation in R. flavipes is targeted to genes with ubiquitous (rather than differential) expression among castes and morphs. A third study examined host transcriptomes of three termite species that included two lower ( Hodotermopsis sjostedti , R. speratus ) and one higher termite ( Nasutitermes takasagoensis ; Hayashi et al, 2013 ). Pyrosequencing was done in combination with 69 caste and phenotypic libraries from the three termite species.…”
Section: Omic Studies In Termites: What Has Been Revealed? mentioning
confidence: 99%